Hourly wage rate and taxable labor income responsiveness to changes in marginal tax rates - Sören Blomquist; Håkan Selin (Uppsala University, Department of Economics, 2008)
Recently, a voluminous literature estimating the taxable income elasticity has emerged as an important field in empirical public economics. However, to a large extent it is still unknown how the hourly wage rate, an important component of taxable income, reacts to changes in marginal tax rates. In this study we use a rich panel data set and a sequence of tax reforms that took place in Sweden during the 1980's to estimate the elasticity of the hourly wage rate with respect to the net-of-tax rate. While carefully accounting for the endogeneity of marginal tax rates as well as other factors that determine wage rates we do find a statistically significant response both among married men and married women. The hourly wage rate elasticity with respect to the net-of-tax rate is estimated to 0.14-0.16 for males and 0.41-0.57 for females. In addition, we obtain uncompensated taxable labor income elasticities of around 0.21 for men and 0.96-1.44 for women. In contrast to earlier studies, we also find significant income effects for males. Accordingly, for males the compensated taxable labor income elasticity is about 4 percentage points higher than the uncompensated one.
urn:nbn:se:uu:diva-87093
Keywords: H24; J22; J31; 330; income taxation; hourly wage rates; work effort; taxable income; Lohnsteuer; Steuerpolitik; Steuertarif; Arbeitsangebot; Zeitlohn; Schweden